Posterior circulation acute stroke prognosis early computed tomography score using hypointense vessels on susceptibility weighted imaging independently predicts outcome in patients with basilar artery occlusion - Mundiyanapurath, Sibu; Möhlenbruch, Markus Alfred; Ringleb, Peter A.; Bösel, Julian; Wick, Wolfgang; Bendszus, Martin; Radbruch, Alexander (PLOS ONE, 2015)
Purpose Appearance of hypointense vessels on susceptibility weighted imaging (SWI) has been reported to correlate with outcome in patients with ischemia of the anterior circulation. This study investigates the correlation between the appearance of hypointense vessels on SWI after recanalization therapy and outcome in patients with basilar artery occlusion. Methods Patients with basilar artery occlusion who were treated with endovascular recanalization or intravenous alteplase and received an MRI including SWI after therapy were retrieved from the hospital database for retrospective analysis. Posterior circulation Acute Stroke Prognosis Early Computed Tomography Score (pcASPECTS) was calculated based on regions displaying hypointense vessels on SWI and compared to lesions on diffusion weighted imaging (DWI). Subsequently, SWI based pcASPECTS was correlated with outcome determined with modified Rankin Scale (mRS), categorized as favorable outcome (mRS 0-2) or unfavorable outcome (3-6). Results Twenty-two MRI of patients with basilar artery occlusion were analyzed. In seven out of eight areas of the pcASPECTS hypointense vessels on SWI were significantly correlated to areas of restricted diffusion on DWI. In univariate analysis median pcASPECTS on SWI was significantly higher in patients with favorable outcome (7.5 vs. 5, p=0.02). In a multivariate analysis pcASPECTS on SWI was an independent predictor of favorable outcome (OR 2.02; CI [1.02;3,99]; p=0.04). Conclusion pcASPECTS based on hypointense vessels on SWI after therapy predicts outcome in patients with basilar artery occlusion and might potentially be used as an additional imaging biomarker in the management of patients with stroke in the posterior circulation. This needs to be confirmed in larger prospective clinical trials.